A STUDY ON ANIDRA WITH SPECIAL REFERENCE TO EFFECT OF BOERHAVIA DIFFUSA (SWETA PUNARNAVA) ON CERTAIN BIO CHEMICAL ALTERATION INDUCED BY SLEEP DEPRIVATION IN RAT (AYUSHDHARA, 2016)
Anidra (disturb sleep) remain a significant health problem in the all age group especially in the elder people till date. Free radical reactions have been implicated in the pathology of many diseases. Sleep deprivation has recently been reported to causes oxidative stress and produces free radicals. B.diffusa has potent anti oxidant activity. The present study was conducted to assess the effect of Boerhavia diffusa (Sweta punarnava) decoction on certain bio chemical alteration induced by sleep deprivation in albino rat. The biochemical study revealed that the enzymatic and non enzymatic anti oxidant in B.biffusa exhibit preventive role to maintains the cell survival, cellular interaction and also maintain the cell membrane architecture. Oxidative stress plays an important role in the patho-physiology of sleep deprivation, and it indicate that the enhancement of oxidative biomarker (Total Glutathione concentration, M.D.A in terms of lipid per oxidation) indicate that chronic sleep deprivation would actually contribute to oxidative stress, but the present study concluded that scientific evaluation of this plant on disturbed sleep is unclear and it has definite role to check oxidative stress.